2006
DOI: 10.1556/abiol.57.2006.1.10
|View full text |Cite
|
Sign up to set email alerts
|

The effects of excess boron with niacin onDaucus carotaL. (Carrot) root callus

Abstract: Niacin (Nicotinic acid, B3 vitamin) may be involved in reduction of toxic effects of boron by regulating growth metabolism. This study was designed to examine whether external niacin treatment would improve the boron mobility in carrot callus cells or not. The results showed that excess boron caused tracheary inversions in meristematic root tissue, and also a shortage was seen in tracheary lengths with boric acid treatment. Boron excess induced the plant tolerance to water stress inverting the tracheary cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In contrast, ABA stimulates root growth (Sharp et al 1994). In a study with carrot (Daucus carota L.) root callus under boron stress, ABA content increased (Demiray and Dereboylu 2006). Our results showed that boron deficient application groups had higher hormone content than excess boron applied groups.…”
Section: Cultivarsmentioning
confidence: 53%
“…In contrast, ABA stimulates root growth (Sharp et al 1994). In a study with carrot (Daucus carota L.) root callus under boron stress, ABA content increased (Demiray and Dereboylu 2006). Our results showed that boron deficient application groups had higher hormone content than excess boron applied groups.…”
Section: Cultivarsmentioning
confidence: 53%
“…[22] Similarly, in a study with carrot (Daucus carota L.) root callus under boron stress, the ABA content also increased. [26] It is presumed that ABA might bind to an apoplastic locus of ABA perception site, inducing an internal calcium-based signal transduction cascade, causing stomatal closure. [27,28] This is a well-known cellular response to abiotic stress conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Three types of modified MS medium (Murashige & Skoog, 1962) were used. Nutritional variants were set: (1) -basic MS supplemented with the addition of 310 mg of H3BO3 and 25 mg of nicotinic acid (Demiray & Dereboylu, 2006); (2) -basic MS medium of Styrax with 0.5 mg of BAP plus 1 mg of NAA and 10 mMol of thiamine pyrophosphate chloride (cocarboxylase) to initiate callus; (3) -basic MS medium supplemented with 0.5 mg of BAP plus 1 mg of NAA as control medium, as a second medium, and as a third medium.…”
Section: Plant Materialsmentioning
confidence: 99%
“…(1) -basic MS supplemented with the addition of 310 mg of H3BO3 and 25 mg of nicotinic acid (Demiray & Dereboylu, 2006); (2) -basic MS medium of Styrax with 0.5 mg of BAP plus 1 mg of NAA and 10 mMol of thiamine pyrophosphate chloride (cocarboxylase) to initiate callus;…”
Section: Plant Materialsmentioning
confidence: 99%